Dampak Manajemen Strategi Pemerintah Kampung Terhadap Pembangunan : Kampung Yoka, Distrik Heram, Kota Jayapura - Daniel Ayub Dawan (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2022)
The obstacles encountered in improving the welfare of rural communities in Indonesia are nearly identical to the problems of community development in Yoka Village, Heram District, Jayapura City, which may be divided into many major issues as follows: 1) The village's communal life is still in its early stages. 2) Village settlements continue to have insufficient services, infrastructure, and facilities; and 3) Government institutions at the local level and socioeconomic institutions have insufficient capacity to support rising village development resources. 4) There is still a lack of connectivity between urban and rural economic activity, which leads to increased economic inequity and gaps in infrastructure services between areas. Yoka village offers a good diversity of potential natural resources. Yoka Village, backed by good soil conditions and the Sentani lake, has become one of the communities that has prospered via the fishing and agricultural industries. The events will be connected to the Yoka Village Government, the Heram District, and Jayapura City. This activity is an essential component of the Village Government Program, which is based on the desires of the Yoka village community as expressed during the Village Deliberation. The program is well-targeted so that the community can implement it and be accountable for it. Aside from that, the Village Government is designed to serve as an extension of the government organization, including the Central/Regional/City and Regency Governments. Of course, we can see the community's advantages here, such as how to use the facilities that have been developed, as well as other activities and the empowerment of micro and small companies that have had an influence